2018
DOI: 10.1136/jnnp-2018-319201
|View full text |Cite
|
Sign up to set email alerts
|

Emotional processing in functional neurological disorder: a review, biopsychosocial model and research agenda

Abstract: Functional neurological disorder (FND) is a common and highly disabling disorder, but its aetiology remains enigmatic. Conceptually, there has been reduced emphasis on the role of psychosocial stressors in recent years, with a corresponding increase in neurobiological explanations. However, a wealth of evidence supports the role of psychosocial adversities (eg, stressful life events, interpersonal difficulties) as important risk factors for FND. Therefore, there is a need to integrate psychosocial (environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
211
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 210 publications
(233 citation statements)
references
References 91 publications
19
211
1
2
Order By: Relevance
“…Our results are also in accordance with functional neuroimaging studies that showed increased activity of limbic and paralimbic regions (Aybek et al 2015;Espay et al 2018;Demartini et al 2019), and alterations in the amygdala, orbitofrontal cortex, and the insula, associated with the abnormal emotional processing in FMD (Voon et al 2010;Pick et al 2019). These regions contribute to the gustatory central process, in terms of quality of the perception, intensity, reward value, and hedonicity rating.…”
Section: Discussionsupporting
confidence: 92%
“…Our results are also in accordance with functional neuroimaging studies that showed increased activity of limbic and paralimbic regions (Aybek et al 2015;Espay et al 2018;Demartini et al 2019), and alterations in the amygdala, orbitofrontal cortex, and the insula, associated with the abnormal emotional processing in FMD (Voon et al 2010;Pick et al 2019). These regions contribute to the gustatory central process, in terms of quality of the perception, intensity, reward value, and hedonicity rating.…”
Section: Discussionsupporting
confidence: 92%
“…More generally, elevated physical symptom burden is associated with significant disability, role impairments and high healthcare use 12 13. Many individuals with FND report significant psychological symptoms/comorbidity (eg, anxiety, depression and dissociation), potentially unhelpful coping behaviours and illness beliefs, and altered emotional processing, which are associated with symptom severity, poorer outcomes and diminished quality of life 10 11 14–23. These factors, therefore, may be particularly relevant to psychosocial outcomes in FND 24 25…”
Section: Introductionmentioning
confidence: 99%
“…A recurring theme from neuroscience studies of patients with functional somatic symptoms is that when the brain stress systems become overactive and over-dominant-that is, get stuck in defensive mode-they over-connect with and disrupt brain regions for motor, sensory, pain, and fatigue processing (Pick et al 2019;Blakemore et al 2016;Vachon-Presseau et al 2016;Sun et al 2020). Disrupted or aberrant processing within these regions is, in turn, expressed in the individual's body as aberrant motor patterns or in her subjective experience as aberrant sensory experiences or as feelings of persisting pain or fatigue.…”
Section: Aberrant Changes In Neural Activation and Connectivitymentioning
confidence: 99%